ONLINE GAMING AND SUSTAINABIITY: A SOCIAL CHALLENGE FOR INTERANTIONAL HUMAN RIHTS LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The booming phenomenon of electronic sports (esports) is, in principle, a powerful tool forinclusion, good health, and well being. It is clear that platforms like Twitch are nowadays a crucialsetting for socialization. It has also been demonstrated that online competitive gaming may help peopleto develop analytical and intellectual skills, spatial coordination, and teamwork. In practice, however,the idea of an inclusive, safe and healthy esports ecosystem is not yet a reality. Hence, against thisepocha l expansion of sport into virtual space, especially during the covid 19 pandemic, this paper aimsto approach a number of legal issues surrounding social sustainability in the online gaming context andthe path towards the possible recognition of the right to play videogames and e sports in internationalhuman rights law.